Application of the Spider Limb Positioner to Subscapular System Free Flaps. (24th August 2020) - Bender‐Heine, Adam; Young, Gavin; Moy, Jennifer; Weedman, Savannah; Wax, Mark K.
Abstract : Objective: To demonstrate the application and surgical time savings of the Spider Limb Positioner for subscapular system free flaps in head and neck reconstructive surgery. Methods: Single institution retrospective chart review and analysis of patients between 2011 and 2019 that underwent a subscapular system free flap either with or without use of the Spider Limb Positioner. One hundred five patients in total were reviewed with 53 patients in the Spider group. The surgical times were compared between the two groups. Patient‐specific information regarding average age, laterality of donor site, recipient site, gender, and flap type were reviewed. Results: Forty‐one patients in both groups underwent a latissimus free flap. Twelve of 53 in the Spider group and 11/52 in the control group underwent a scapula free flap. The average age in the Spider group at the time of surgery was 64 years. The recipient sites for the Spider groups were reviewed. The free flap was ipsilateral to the defect in 81% of cases. The mean surgical time for the 105 patients without the Spider was 568 minutes versus 486 minutes with a Spider P ‐value of .003478. Conclusion: Use of the Spider Limb Positioner allows for a simultaneous two‐team approach during free flap elevation of the subscapular system, which eliminates both dependence on an assistant to support the arm and time consuming positioning changes during flap elevation. Level of Evidence: 3 Laryngoscope, 131:525–528, 2021